Increasing Data Anonymity using AES and Privacy Technique - Thamer Khalil, Esmeel; Roslina, Abd Hamid; Rahmah, Mokhtar (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Data security and data preserve privacy had been an important area to a huge in recent years. However, rapid developments in collecting, analyzing, and using personal data had made privacy a very important issue. This thesis had addressed the problem the protect user data in the dataset from attacks internal and attacks external by using combination techniques between security technique, and privacy techniqueand data mining technique. The research objectives were to determine the privacy and security technique in suitable the dataset, and to implement the combination property with chosen and security technique in order to protect user data in the dataset and to validate by comparing result before and after apply privacy techniques in dataset using chosen data mining tool. The research methodology consists of three phases. the analysis phase, combination techniques phase, and results evaluating phase and for every phase has research objective.